Przetwórstwo żywca wieprzowego na Podkarpaciu po wejściu Polski do Unii Europejskiej - Stec, Artur; Kusz, Dariusz (Porkers Processing Sector in Podkarpackie Province after the Accession of Poland to European Union, 2006)
The accession of Poland to the European Union becam a major reason of porkers processing sector transformation in Podkarpackie Province. The number of meat plants decreased from 116 to 114 in the region from 10 April 2004 to 31 December 2005. At the same time the adaptation (processes of meat plants to the union standards increased. Before the Polish accession to the union structures there were 3% of plants in category A, whereas at the end of year 2005 over 20%. In the case of production capacity proportions developed even more favourably, over 10% and over 80% respectively.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 345-349